Digital photographs classification - Low, Amy Ghee Teng. (2010)
The number of people taking up digital photography as a hobby or using a digital camera as a lifestyle tool has gained widespread increase over recent years. As such users are getting to have large collections of digital photographs. Organization and management of those large personal image collections is a laborious task. Thus it becomes an arising challenge.